Susceptibility patterns in Neisseria gonorrhoeae in Nuuk, Greenland, 2015-2018: a short communication. Issue 1 (1st January 2019) - Berntsen, Sine; Mulvad, Gert; Jensen, Jørgen Skov; Poulsen, Peter; Hansen, Henrik Lyngbeck; Pedersen, Michael Lynge
ABSTRACT: Antimicrobial resistance in Neisseria gonorrhoeae (GC) has made gonorrhoea control and treatment more complex globally. In Greenland, the incidence of gonorrhoea is high and there is a need for continued surveillance of antimicrobial susceptibility. This study investigated gonococcal isolates obtained in Greenland's capital Nuuk between January 2015 and June 2018. Subsequent to collection, isolates were tested for ciprofloxacin and ceftriaxone susceptibility in order to monitor the resistance pattern among GC strains. 150 GC strains were isolated in Nuuk during the observation period (139 males, 93%; 11 females, 7%). All strains were fully susceptible to ceftriaxone. 49% of the GC strains were susceptible to ciprofloxacin. The median minimal inhibitory concentration (MIC) for ceftriaxone among GC strains resistant to ciprofloxacin was higher than among GC strains susceptible to ciprofloxacin. No differences in ciprofloxacin susceptibility and median MICs for ceftriaxone were observed by collection year. In conclusion no ceftriaxone resistance has been found in Nuuk to date. Continued easy access to diagnostics and treatment combined with increased and more systematic surveillance of antimicrobial susceptibility in Nuuk is recommended. Further, it is advisable to investigate the possibilities for intermittent sampling in Greenland outside of Nuuk, if obstacles in relation to sending sampling material to Nuuk can be bypassed.